Anomalies in internal-conversion coefficients of the K-forbidden gamma-transitions from the 177mLu decay - A. P. Lashko; T. N. Lashko (Ядерна фізика та енергетика)
Some sections of the 177mLu conversion electron spectra were measured by means of π 2 magnetic β-spectrometer. Relative intensities of internal-conversion electron lines and absolute values of internal conversion coefficients on L-subshells of 177Lu for γ116 keV transition were determined with high precision. The experimental data were compared with theoretical values.